Review of Applications of Quantum Computing in Power Flow Calculation - Jang, Ye-Eun; Kim, Na-Yeon; Kim, Young-Jin (Journal of electrical engineering & technology, 2024)
The proliferation of distributed energy resources has increased the complexity of power system analysis and operation. To address the complexity, various algorithms have been studied on classical computers, but their performance was constrained by hardware limitations of classical computers. As a new computing paradigm, quantum computing has recently been applied to power system operations to enhance computational efficiency, and early studies on quantum computing application have demonstrated the computational efficiency. Although there remains the limited scalability in current quantum devices, various algorithms have been developed by combining classical and quantum computers to exploit quantum computing fully. Therefore, with the brief introduction of quantum computing and its computing systems, this paper reviews and discusses the recent studies particularly on power flow and optimal power flow calculations using various quantum algorithms ranging from pure quantum computing algorithms to hybrid quantum-classical algorithms. In addition, this paper suggests new research subjects in power flow calculations for future studies.